Examining the judgments of pedophiles in relation to a non-sexual offense - Maroño, Abbie (Psychology, crime & law, 2020)
Even though pedophilia is not synonymous with child sexual abuse, it remains a highly stigmatized phenomenon. As such, non-offending pedophilic individuals are judged as being dangerous, abnormal, amoral, and in need of punishment. It is unknown, however, whether a pedophilic individual would be judged more harshly than a heterosexual individual and a homosexual individual in relation to a nonsexual, nonviolent offense. This was the aim of the present study. A final sample of 309 participants were recruited online and allocated to one of three sexual orientation conditions. Participants read the same hypothetical crime report (breaking and entering) followed by a suspect profile that was identical across conditions except for sexual orientation. They then provided sentencing and moral character judgements of the suspect. Participants also completed a punitive attitudes scale pertaining to pedophilia. Results showed that the pedophilic individual received harsher judgments relative to the heterosexual individual, but only at higher levels of pre-existing punitive attitudes. These findings suggest that anti-pedophilia stigma can bias judgments about offenses that are not sexual. We argue that this is due to a ‘reverse halo effect’. However, we consider an alternative explanation based on the idea of interpreting information in a schema-consistent manner. Limitations and suggestions for future research are discussed.